2021
DOI: 10.2147/oaem.s297850
|View full text |Cite
|
Sign up to set email alerts
|

New Horizons in Understanding Appropriate Prehospital Identification and Trauma Triage for Older Adults

Abstract: Caring for older people is an important part of prehospital practice, including appropriate triage and transportation decisions. However, prehospital triage criteria are designed to predominantly assess injury severity or high-energy mechanism which is not the case for older people who often have injuries compounded by multimorbidity and frailty. This has led to high rates of under-triage in this population. This narrative review aimed to assess aspects other than triage criteria to better understand and impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 66 publications
2
8
0
Order By: Relevance
“…The treatment at TCs was, however, shown to increase the length of in-hospital stay and costs. These findings were consistent with other research findings which showed an inconclusive survival benefit of TC access for this population [62].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The treatment at TCs was, however, shown to increase the length of in-hospital stay and costs. These findings were consistent with other research findings which showed an inconclusive survival benefit of TC access for this population [62].…”
Section: Discussionsupporting
confidence: 93%
“…This could adversely affect the accuracy of prehospital trauma triage tools even when geriatric-specific triage criteria were developed to adjust for age-related anatomical and physiological changes, comorbidities, and medication use [61], as shown in this review. Therefore, integrating other assessment tools, such as frailty, into the trauma triage tool may improve the identification of high-risk patients and reduce under-triage [62]. However, paramedics' compliance to trauma triage tools was shown to decrease with patients aged ≥ 55 years compared to younger adults [63], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“… 7 Current triage and management guidelines in prehospital care and are not clear about how to optimise the level of care provided to this population. 8 For example, recent evidence showed that most current and developed geriatric-specific trauma triage criteria applied in prehospital care were not accurate in identifying older patients who had high injury severity and/or required trauma center care. 9 This is potentially due to the fact that prehospital triage criteria and paramedics’ judgments on how to manage patients are predominantly reliant on physiological variables.…”
Section: Introductionmentioning
confidence: 99%